(untitled) (Bangladesh Journal of Agricultural Research, 2016)
The experiment was conducted to study the effect of honey bee pollination and curd scooping on seed production of cauliflower (Brassica oleracea var. botrytis L.) cv. Poushali. Eighteen combinations of treatments comprising three types of pollination viz., open pollination (natural pollination), using bees for pollination inside net (planned pollination) and plants inside net without bees (control) and six kinds of curd scooping viz., 25%, 50% and 75% of curd cutting, cross curd cutting, central curd cutting and no curd cutting (control). Honey bee (Apis cerana L.) was used as pollinator. Seed yield and yield attributes were significantly influenced by both factors and their combinations. Central curd cutting influenced early flowering and siliqua maturity compared to other curd cutting treatments. Planned honey bee pollination was found to inflict maximum impact on the seed production of cauliflower with an increase in seed yield of 45.46% and 23.17% higher over plants grown inside net without bees and open pollination, respectively. Central curd scooping increased 26.52% higher yield than that of no curd cutting treatment. Planned bee pollination and central curd cutting independently as well as in combination gave the maximum yield attributes of seed viz., primary and secondary flower stalks/plant, number of siliquas/plant, length of siliqua, number of seeds/siliqua,1000 seed weight, seed yield and seed germination percent of cauliflower. Planned pollination coupled with central curd cutting gave the maximum seed yield of 607.43 kg/ha in cauliflower. Bangladesh J. Agril. Res. 41(2): 251-258, June 2016